2015
DOI: 10.3109/0886022x.2015.1068031
|View full text |Cite
|
Sign up to set email alerts
|

Role of ERK1/2 and JNK phosphorylation in iodine contrast agent-induced apoptosis in diabetic rat kidneys

Abstract: Background: The risk of contrast-induced acute kidney injury (CIAKI) is significantly increased in patients with diabetes mellitus. This study aimed to investigate molecular mechanisms of contrast media-induced apoptosis in diabetic rat kidneys, especially the involvement of ERK1/2 and JNK signal pathways. Methods: Diabetic Sprague-Dawley rats were induced by intraperitoneal injection of streptozotocin. Ten weeks later the normal and diabetic rats were administered high-osmolar contrast media (HOCM; meglumine … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 30 publications
1
12
1
Order By: Relevance
“…There is evidence of similar roles of JNK and p38 and vice versa. Contrary to our findings, a previous study provides evidence for a protective role of ERK against contrast-induced nephropathy in vivo [ 45 ]. In the present study, treatment with U0126 attenuates iodixanol-induced LLC-PK1 cell death and this protective effect was synergistic when treated with 5 μM of compound 8 .…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…There is evidence of similar roles of JNK and p38 and vice versa. Contrary to our findings, a previous study provides evidence for a protective role of ERK against contrast-induced nephropathy in vivo [ 45 ]. In the present study, treatment with U0126 attenuates iodixanol-induced LLC-PK1 cell death and this protective effect was synergistic when treated with 5 μM of compound 8 .…”
Section: Discussioncontrasting
confidence: 99%
“…In our study, pretreatment with compound 8 inhibited the phosphorylation of ERK, JNK, and p38 induced by iodixanol. Studies have reported that JNK and p38 induced by oxidative stress regulate apoptosis against contrast-induced nephropathy in vitro and in vivo [ 44 , 45 ]. In contrast, the role of ERK remains less clear than that of JNK and p38 and remains controversial, with conflicting evidence.…”
Section: Discussionmentioning
confidence: 99%
“…For example, some studies showed that the activation of ERK1/2 signaling pathway in the human kidney with glomerulopathies correlated with cell proliferation, histologic lesions, renal fibrosis and dysfunction [33], while other work suggests that apoptosis in diabetic rat kidneys is likely related to a decrease in phosphorylated ERK1/2 levels and an increase in phosphorylated JNK levels [34]. A better understanding of renal MAPK function under hypoxic/ischemic conditions may therefore…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that phosphorylation of MAPKs is upregulated in the kidneys of STZ-induced diabetic rats. 34 Hence, we assessed the role of RAP treatment on MAPK activation by examining the phosphorylation of ERK1/2 and p38 using immunohistochemical analysis. The results showed that the positive areas of phosphorylated ERK1/2 and p38 staining were markedly increased in STZ-induced diabetic kidneys compared to normal control kidneys.…”
Section: Resultsmentioning
confidence: 99%